Analysis of Non-Technical Losses in Distributed Transformer System (International Journal of Engineering and Computer Science, 2016)
Electrical Energy Audit consists of Studying, Assessing, Measuring and Analyzing electrical utilities. In short, the audit is designed to determine where, when, why and how energy is being used. This information can then be used to identify opportunities to improve efficiency, decrease energy costs and reduce greenhouse gas emissions that contribute to climate change. Just as financial accounting is used for the effective management of an organization, energy accounting is critical to energy management. It can be one of the most cost-effective tools for industries to cut energy costs.India’s power sector is characterized by inadequate and inefficient power supply. In this we have to proposed survey of power losses in Okhala station. We have to survey 24 DT’s of Okhala station. Result is analyzed by Matlab tool. Graph of different DT’s is analyzed according to different months & total power losses.